Rare-earth-based nano-composite hydrogel wound dressing as well as preparation method and application thereof

By optimizing the preparation process of rare earth-based nanocomposite hydrogel wound dressing, the composite stability problem of rare earth elements and carbomer gel is solved, the uniformity and stability of wound dressing is achieved, and the wound healing effect and antibacterial performance are improved.

CN120420495APending Publication Date: 2025-08-05INNER MONGOLIA ZHONGTIAN HONGYUAN RARE EARTH NEW MATERIAL
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
CN202510638028.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-05-16
Publication Date
2025-08-05

AI Technical Summary

Technical Problem

Existing wound dressings have limitations in keeping wounds moist, promoting healing and preventing infection. How to achieve effective composite of rare earth elements with carbomer gel and ensure the stability and uniformity of the dressings has become an urgent problem.

Method used

By optimizing the preparation process, including predispersion, ultrasonic dispersion, step-by-step water addition and stabilizing agent, we ensure the uniform mixing and stability of each component in the rare earth-based nanocomposite hydrogel wound dressing to form a stable gel system.

Benefits of technology

It significantly improves the performance consistency and product quality of the dressing, promotes wound healing and tissue regeneration, reduces bubble generation, and maintains long-term stability of antibacterial and scar repair performance.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005407767040000121
    Figure BDA0005407767040000121
  • Figure BDA0005407767040000131
    Figure BDA0005407767040000131
Patent Text Reader

Abstract

The invention relates to the technical field of wound dressings, in particular to a rare-earth-based nano-composite hydrogel wound dressing and a preparation method and application thereof.The preparation method comprises the following steps that gel powder is added into a dispersing agent to be pre-dispersed, and gel dispersion liquid is obtained; adding a compound containing rare earth elements and / or rare earth nanoparticles into a dispersing agent for pre-dispersion to obtain a rare earth dispersion liquid; adding the gel dispersion liquid into the rare earth dispersion liquid at the temperature of 30-40 DEG C, adding part of deionized water, stirring for preliminary swelling, and then adding the rest deionized water in a stirring state until a gel dressing is formed; and adding a stabilizer into the gelatinous dressing, and stirring for reaction to obtain the rare-earth-based nano composite hydrogel wound dressing. According to the rare-earth-based nano-composite hydrogel wound dressing and the preparation method and application thereof, the mixing uniformity and stability of all the components in the dressing are improved, and therefore the performance of the dressing in the aspect of promoting wound healing is improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of wound dressings, in particular to a rare earth-based nanocomposite hydrogel wound dressing and a preparation method and application thereof. Background Art

[0002] Wound dressings play a vital role in wound treatment. Traditional wound dressings have certain limitations in maintaining wound moisture, promoting healing, and preventing infection. With the advancement of technology, new wound dressings with multifunctional properties such as antibacterial and tissue repair have become a research hotspot. Carbomer gel has good biocompatibility and water retention, and rare earth elements and their compounds exhibit unique antibacterial and antioxidant properties. Combining the two is expected to develop high-performance wound dressings. However, how to achieve an effective combination of the two and ensure the stability, uniformity, and safety of the dressing has become an urgent problem to be solved. Summary of the Invention

[0003] The purpose of the present invention is to provide a rare earth-based nanocomposite hydrogel wound dressing, a preparation method and application thereof, and to improve the mixing uniformity and stability of the ingredients in the dressing by optimizing the preparation process, thereby enhancing the performance of the dressing in promoting wound healing.

[0004] To achieve the above object, the present invention provides a method for preparing a rare earth-based nanocomposite hydrogel wound dressing, comprising the following steps:

[0005] S1. Adding gel powder to a dispersant for pre-dispersion to obtain a gel dispersion, and adding a rare earth element-containing compound and / or rare earth nanoparticles to a dispersant for pre-dispersion to obtain a rare earth dispersion;

[0006] S2. Add the gel dispersion to the rare earth dispersion at a temperature of 30-40° C., add a portion of deionized water, stir for preliminary swelling, and then add the remaining deionized water while stirring until a gel-like dressing is formed;

[0007] S3. Add a stabilizer to the gel dressing in S2, and stir to react to obtain a rare earth-based nanocomposite hydrogel wound dressing.

[0008] Preferably, in S1, the gel powder is carbomer, and the rare earth element-containing compound and / or rare earth nanoparticles are one or more of organic or inorganic salts of lanthanum and cerium, and nanoparticles of lanthanum oxide and cerium oxide;

[0009] The mass ratio of the gel powder to the compound containing rare earth elements and / or rare earth nanoparticles is 1-3:1.

[0010] Preferably, in S1, the dispersant is one of polyvinyl pyrrolidone, sodium lauryl sulfate, and polyethylene glycol;

[0011] In S1, the mass of the dispersant in the gel dispersion is 10%-15% of the mass of the gel powder, and the mass of the dispersant in the rare earth dispersion is 8%-12% of the mass of the rare earth element-containing compound and / or rare earth nanoparticles.

[0012] Preferably, in S1, the pre-dispersion of the gel dispersion is carried out by ultrasonic dispersion at an ultrasonic frequency of 30-60 kHz for 10-30 minutes, and the pre-dispersion of the rare earth dispersion is carried out by continuous stirring at a stirring speed of 1200-1800 r / min for 10-30 minutes.

[0013] Preferably, in S2, the volume ratio of the total amount of deionized water to the gel dispersion is 10:1.

[0014] Preferably, in S2, the stirring speed of the initial swelling is 60-80 r / min, and the stirring time is 10-20 min. After the remaining deionized water is added, the stirring speed is 80-100 r / min, and the stirring time is 20-30 min.

[0015] Preferably, in S3, the stabilizer is one of sodium alginate and chitosan, and the amount of the stabilizer is 0.5%-2% of the total mass of the gel dressing.

[0016] Preferably, in S3, the stirring reaction is carried out at a stirring speed of 120-180 r / min and the stirring is continued for 20-40 min.

[0017] The present invention also provides a rare earth-based nanocomposite hydrogel wound dressing prepared by the preparation method of the rare earth-based nanocomposite hydrogel wound dressing.

[0018] The present invention also provides an application of the rare earth-based nanocomposite hydrogel wound dressing, which is applied to the preparation of drugs for promoting wound healing and tissue regeneration.

[0019] Beneficial effects of the present invention:

[0020] (1) The present invention adopts the above-mentioned rare earth-based nanocomposite hydrogel wound dressing and its preparation method and application. Through the pre-dispersion step, ultrasonic dispersion and high-speed stirring are used to effectively break the agglomeration of gel powder and rare earth element-containing compounds and / or rare earth nanoparticles, increase the contact area between the two, significantly improve the uniformity of subsequent mixing, and thus improve the consistency of dressing performance.

[0021] (2) The present invention adopts the above-mentioned rare earth-based nanocomposite hydrogel wound dressing and its preparation method and application, and strictly controls the temperature, amount of water added, stirring speed and time during the blending process, which helps the gel molecules to swell and disperse better, fully interact with the rare earth components, form a stable and high-performance gel system, reduce bubble generation, and improve product quality.

[0022] (3) The present invention adopts the above-mentioned rare earth-based nanocomposite hydrogel wound dressing and its preparation method and application. By adding a stabilizer, it can form an interactive network with the gel molecules and rare earth element-containing compounds and / or rare earth nanoparticles, preventing the gel from stratification, precipitation, etc. during storage, and maintaining its antibacterial and scar repair properties for a long time.

[0023] The technical solution of the present invention is further described in detail below through examples. DETAILED DESCRIPTION

[0024] The present invention will be further described below with reference to the following embodiments. Unless otherwise defined, technical or scientific terms used herein shall have the same meanings as those commonly understood by persons of ordinary skill in the art to which the present invention pertains. The above-mentioned features or features described in the specific examples of the present invention may be combined in any manner. These specific embodiments are intended only to illustrate the present invention and are not intended to limit the scope of the present invention.

[0025] The present invention provides a method for preparing a rare earth-based nanocomposite hydrogel wound dressing, comprising the following steps:

[0026] S1. Adding gel powder to a dispersant for pre-dispersion to obtain a gel dispersion, and adding a rare earth element-containing compound and / or rare earth nanoparticles to a dispersant for pre-dispersion to obtain a rare earth dispersion;

[0027] S2. Add the gel dispersion to the rare earth dispersion at a temperature of 30-40° C., add a portion of deionized water, stir for preliminary swelling, and then add the remaining deionized water while stirring until a gel-like dressing is formed;

[0028] S3. Add a stabilizer to the gel dressing in S2, and stir to react to obtain a rare earth-based nanocomposite hydrogel wound dressing.

[0029] Preferably, in S1, the gel powder is carbomer, and the rare earth element-containing compound and / or rare earth nanoparticles are one or more of organic or inorganic salts of lanthanum and cerium, and nanoparticles of lanthanum oxide and cerium oxide;

[0030] In some embodiments of the present invention, the rare earth element-containing compound and / or rare earth nanoparticles are one of lanthanum nitrate, lanthanum chloride, cerium nitrate, cerium sulfate, lanthanum oxide, and cerium dioxide nanoparticles;

[0031] The mass ratio of the gel powder to the compound containing rare earth elements and / or rare earth nanoparticles is 1-3:1.

[0032] In some embodiments of the present invention, the mass ratio of the gel powder to the rare earth element-containing compound and / or rare earth nanoparticles is 3:1.

[0033] Preferably, in S1, the dispersant is one of polyvinyl pyrrolidone, sodium lauryl sulfate, and polyethylene glycol;

[0034] In S1, the mass of the dispersant in the gel dispersion is 10%-15% of the mass of the gel powder, and the mass of the dispersant in the rare earth dispersion is 8%-12% of the mass of the rare earth element-containing compound and / or rare earth nanoparticles.

[0035] In some embodiments of the present invention, in S1, the mass of the dispersant in the gel dispersion is 12% of the mass of the gel powder, and the mass of the dispersant in the rare earth dispersion is 10% of the mass of the rare earth element-containing compound and / or rare earth nanoparticles.

[0036] The present invention reduces the surface tension between gel powder and compounds containing rare earth elements and / or rare earth nanoparticles by adding a dispersant, prevents particle agglomeration, and makes the gel powder and compounds containing rare earth elements and / or rare earth nanoparticles uniformly dispersed therein to form a stable suspension.

[0037] Preferably, in S1, the pre-dispersion of the gel dispersion is carried out by ultrasonic dispersion at an ultrasonic frequency of 30-60 kHz for 10-30 minutes, and the pre-dispersion of the rare earth dispersion is carried out by continuous stirring at a stirring speed of 1200-1800 r / min for 10-30 minutes.

[0038] In some embodiments of the present invention, in S1, the pre-dispersion of the gel dispersion is carried out by ultrasonic dispersion at an ultrasonic frequency of 40 kHz for 15 minutes, and the pre-dispersion of the rare earth dispersion is carried out by continuous stirring at a stirring speed of 1500 r / min for 20 minutes.

[0039] The present invention uses ultrasonic dispersion or high-speed stirring to uniformly disperse gel powder and rare earth element-containing compounds and / or rare earth nanoparticles in a dispersant to form a stable suspension, thereby increasing the contact area between the two powders and significantly improving the uniformity of subsequent mixing. In addition, the pre-dispersion treatment can effectively break up agglomerates of nano-scale rare earth particles, allowing them to be better mixed with the gel powder.

[0040] Preferably, in S2, the volume ratio of the total amount of deionized water to the gel dispersion is 10:1.

[0041] In the present invention S2, by controlling the temperature during the blending of the gel dispersion and the rare earth dispersion, the gel molecules are better able to swell and disperse, fully interacting with the rare earth components, and forming a more stable gel system with excellent performance. Temperature control also helps reduce bubbles that may form during the blending process, thereby improving product quality.

[0042] Preferably, in S2, the stirring speed of the initial swelling is 60-80 r / min, and the stirring time is 10-20 min. After the remaining deionized water is added, the stirring speed is 80-100 r / min, and the stirring time is 20-30 min.

[0043] In some embodiments of the present invention, in S2, the stirring speed of the initial swelling is 65 r / min, and the stirring time is 15 min. After the remaining deionized water is added, the stirring speed is 90 r / min, and the stirring time is 25 min.

[0044] The present invention adopts a step-by-step water addition method. A portion of water is first added to initially swell the gel powder and form a relatively uniform paste. The remaining water is then slowly added while stirring, and stirring is continued until the desired gel is formed. This avoids the uneven concentration caused by adding too much water at once, which can affect the formation and performance of the gel.

[0045] Preferably, in S3, the stabilizer is one of sodium alginate and chitosan, and the amount of the stabilizer is 0.5%-2% of the total mass of the gel dressing.

[0046] In some embodiments of the present invention, in S3, the amount of the stabilizer is 1.5% of the total mass of the gel-like dressing.

[0047] In the present invention, a stabilizer is added to form an interactive network with the gel molecules and the rare earth element-containing compound and / or rare earth nanoparticles to enhance the stability of the gel system. The addition of the stabilizer can not only prevent the gel from stratification, precipitation and the like during storage, but also maintain its long-term stability in antibacterial and scar repair properties.

[0048] Preferably, in S3, the stirring reaction is carried out at a stirring speed of 120-180 r / min and the stirring is continued for 20-40 min.

[0049] In some embodiments of the present invention, in S3, the stirring reaction is continued at a stirring speed of 160 r / min for 30 min.

[0050] The present invention also provides a rare earth-based nanocomposite hydrogel wound dressing prepared by the preparation method of the rare earth-based nanocomposite hydrogel wound dressing.

[0051] The present invention also provides an application of the rare earth-based nanocomposite hydrogel wound dressing, which is applied to the preparation of drugs for promoting wound healing and tissue regeneration.

[0052] Example 1

[0053] The present invention provides a method for preparing a rare earth-based nanocomposite hydrogel wound dressing, comprising the following steps:

[0054] S1. Add 300 g of carbomer gel powder to 36 g of polyvinyl pyrrolidone, and perform ultrasonic dispersion for 15 min at an ultrasonic frequency of 40 kHz to obtain a gel dispersion.

[0055] 100 g of lanthanum nitrate rice particles were added to 10 g of polyvinyl pyrrolidone, and the mixture was stirred at a stirring speed of 1500 r / min for 20 min to perform pre-dispersion to obtain a rare earth dispersion.

[0056] S2. Measure 3000 mL of deionized water and add the gel dispersion to the rare earth dispersion at 35°C. Add 1500 mL of deionized water and stir at 65 rpm for 15 minutes to allow for initial swelling. Then, while stirring, add the remaining 1500 mL of deionized water and increase the stirring speed to 90 rpm. Continue stirring for 25 minutes until a gel-like dressing is formed.

[0057] S3. Add sodium alginate stabilizer to the gel dressing in S2, and continue stirring at a stirring speed of 160 r / min for 30 minutes to obtain a rare earth-based nanocomposite hydrogel wound dressing.

[0058] Example 2

[0059] The difference from Example 1 is that the amount of carbomer gel powder in the gel dispersion in S1 is 100 g, and the amount of polyvinyl pyrrolidone is 10 g. Other contents are the same as in Example 1.

[0060] Example 3

[0061] The difference from Example 1 is that the amount of carbomer gel powder in the gel dispersion in S1 is 200 g, and the amount of polyvinyl pyrrolidone is 30 g. Others are the same as in Example 1.

[0062] Example 4

[0063] The difference from Example 1 is that the amount of polyvinyl pyrrolidone used in the rare earth dispersion in S1 is 8 g, and the rest is the same as Example 1.

[0064] Example 5

[0065] The difference from Example 1 is that the amount of polyvinyl pyrrolidone used in the rare earth dispersion in S1 is 12 g, and the rest is the same as Example 1.

[0066] Example 6

[0067] The difference from Example 1 is that the dispersant of the gel dispersion and the rare earth dispersion in S1 is sodium lauryl sulfate, and the rest is the same as Example 1.

[0068] Example 7

[0069] The difference from Example 1 is that the dispersant of the gel dispersion and the rare earth dispersion in S1 is polyethylene glycol, and the rest is the same as Example 1.

[0070] Example 7

[0071] The difference from Example 1 is that the rare earth element-containing compounds and / or rare earth nanoparticles in S1 are lanthanum chloride, cerium nitrate, cerium sulfate, lanthanum oxide, and cerium dioxide nanoparticles, respectively. The rest are the same as in Example 1.

[0072] Example 8

[0073] The difference from Example 1 is that in S1, the pre-dispersion of the gel dispersion is ultrasonic dispersion at an ultrasonic frequency of 30 kHz for 30 min, and the pre-dispersion of the rare earth dispersion is continuous stirring at a stirring speed of 1200 r / min for 30 min. The rest is the same as in Example 1.

[0074] Example 9

[0075] The difference from Example 1 is that in S1, the pre-dispersion of the gel dispersion is ultrasonic dispersion at an ultrasonic frequency of 60 kHz for 10 min, and the pre-dispersion of the rare earth dispersion is continuous stirring at a stirring speed of 1800 r / min for 10 min. The rest is the same as in Example 1.

[0076] Example 10

[0077] The difference from Example 1 is that in S2, the stirring speed of the initial swelling is 60 r / min and the stirring time is 20 min. After the remaining deionized water is added, the stirring speed is 80 r / min and the stirring time is 30 min. The rest is the same as Example 1.

[0078] Example 11

[0079] The difference from Example 1 is that in S2, the stirring speed of the initial swelling is 80 r / min and the stirring time is 10 min. After the remaining deionized water is added, the stirring speed is 100 r / min and the stirring time is 20 min. The rest is the same as Example 1.

[0080] Example 12

[0081] The difference from Example 1 is that the stabilizer is chitosan, and the amount of the stabilizer is 0.5% of the total mass of the gel-like dressing. Other aspects are the same as Example 1.

[0082] Example 13

[0083] The difference from Example 1 is that the stabilizer is sodium alginate, and the amount of the stabilizer is 2% of the total mass of the gel-like dressing. Other aspects are the same as Example 1.

[0084] Example 14

[0085] The difference from Example 1 is that in S3, the stirring reaction is carried out at a stirring speed of 120 r / min and the stirring is continued for 40 min. The other steps are the same as in Example 1.

[0086] Example 15

[0087] The difference from Example 1 is that in S3, the stirring reaction is carried out at a stirring speed of 180 r / min and the stirring is continued for 20 min. The other steps are the same as in Example 1.

[0088] Comparative Example 1

[0089] The difference from Example 1 is that in S1, the carbomer gel powder and the lanthanum nitrate rice particles are directly mixed without pre-dispersion, and the subsequent steps are the same as in Example 1.

[0090] Comparative Example 2

[0091] The difference from Example 1 is that the deionized water in S2 is added all at once without adding in steps. The other steps are the same as in Example 1.

[0092] Comparative Example 3

[0093] The difference from Example 1 is that the step of adding a stabilizer in S3 is not performed, and the rest is the same as Example 1.

[0094] Performance Testing

[0095] Cytotoxicity test: The frozen mouse epithelial fibroblast L929 was thawed and cultured. After the culture was completed, 100 μL of L929 cell suspension (5000 cells / well) was inoculated into a 96-well plate and placed in an incubator overnight. Then, 100 μL of the rare earth-based nanocomposite hydrogel wound dressing of Examples 1-3 and Comparative Examples 1-3 was added to the culture plate wells. Six replicate wells were set for each group, and DMEM culture medium (Dulbecco's modified Eagle's medium) without addition was used as a control group. After 24 hours of culture, 10% MTT solution (tetramethylthiazolium salt solution) was added to each well. After incubation in the dark for 4 hours, 150 μL of DMSO (dimethyl sulfoxide) was added to each well, shaken on a shaker for 20 minutes, and the absorbance of the cells was detected using a microplate reader.

[0096] The MTT assay was used to quantitatively determine in vitro cytotoxicity. As shown in Table 1, the absorbance values of the cells in Examples 1-3 were all higher than that in the control group, while the absorbance values of the cells in Comparative Examples 1-3 were all lower than that in the control group. This indicates that the composite hydrogel rare earth-based nanocomposite hydrogel wound dressing has no toxic side effects and can improve cell viability to a certain extent.

[0097] Table 1 MTT method to determine the absorbance of cells

[0098]

[0099] This is because the pre-dispersion step of the embodiment of the present invention fully disperses the carbomer gel powder and the compound containing rare earth elements and / or rare earth nanoparticles, greatly increasing the contact area between the two. In the subsequent blending process, the two can be mixed more evenly. Moreover, at a suitable temperature, the carbomer gel powder fully swells and interweaves with the rare earth components to form a stable and high-performance gel system. This structure provides a stable and suitable microenvironment for cells. The added sodium alginate or chitosan stabilizer forms an interactive network with the carbomer gel powder and the rare earth components, maintaining the stability of the system, so that the dressing can continue to slowly release components that are beneficial to cells. For example, rare earth elements may reduce harmful substances in the environment surrounding cells through their own antibacterial and antioxidant properties, reduce cell stress, thereby promoting cell growth and differentiation, and improving cell viability, which is manifested as a higher cell absorbance value.

[0100] Comparative Example 1, however, omitted the pre-dispersion step and directly mixed the carbomer gel powder with the rare earth element-containing compound and / or rare earth nanoparticles, resulting in poor mixing uniformity and agglomeration. Agglomerated particles can cause localized over-concentration. Comparative Example 2, in which all deionized water was added at once during the blending process, resulted in uneven local concentrations in the gel dressing. In areas of excessively high concentration, the osmotic pressure of the environment surrounding cells is unbalanced, affecting their normal morphology and function. High concentrations of rare earth ions can disrupt intracellular ion balance and enzyme activity, disrupting cellular metabolism and leading to reduced mitochondrial succinate dehydrogenase activity. In areas of excessively low concentration, cells are unable to obtain sufficient nutrients and beneficial components, affecting cell growth.

[0101] In Comparative Example 3, no stabilizer was added during the preparation process, resulting in poor stability and easy delamination of the hydrogel dressing. An unstable system cannot provide a continuously stable environment for cells. Unbalanced release of components can expose cells to excessively high or low concentrations of substances at any given moment, causing damage, disrupting normal metabolic pathways within cells, and inhibiting mitochondrial succinate dehydrogenase activity, ultimately resulting in lower cell absorbance values than the control group.

[0102] Skin wound repair experiment: In order to evaluate the wound healing efficiency and tissue regeneration effect of photopolymerized composite hydrogel in vivo, the most common and main skin wound model was established on the dorsal side of rats. After depilation and anesthesia, SD male rats (250 g) were anesthetized and full-thickness skin injuries (7 mm in diameter) were caused on their backs. All rats were divided into three groups (n=3), and the back wounds were treated differently: a control group smeared with normal saline, Example 4-6 groups, and Comparative Example 1-3 groups. The injected composite hydrogel mixture contained a photoinitiator LAP (2-hydroxy-2-methyl-1-phenylpropanone) (0.5 wt%). The wound healing condition was observed and photographed on different days. The wound area was measured using Image J software, and the wound healing rate was statistically analyzed.

[0103] The formula for calculating wound healing rate is as follows: Wound healing rate = S n / S0×100%;

[0104] Among them S n and S0 represent the wound areas on day n and day 0, respectively.

[0105] The results are shown in Table 2. Within 10 days, the wound areas of all groups gradually decreased over time. On the 10th day, the groups of Examples 4-6 all showed the best wound healing effect, with wound healing rates of 91.3%, 92.8%, and 92.1%, respectively, which were higher than 85.2% of the control group. On the 10th day, the wound healing rates of the groups of Comparative Examples 1-3 were 82.1%, 81.4%, and 80.5%, respectively, which were lower than the control group.

[0106] Table 2 Wound healing rates of different treatment groups on day 10

[0107]

[0108] This is because in the preparation process of Examples 4-6 of the present invention, the carbomer gel powder and the compound containing rare earth elements and / or rare earth nanoparticles were pre-dispersed by ultrasound and stirring, and were evenly distributed in the dispersant. The contact area was large during mixing, creating a stable microenvironment for wound cells and promoting cell migration and proliferation. During the reconciliation, deionized water was added step by step, and the stirring speed and time at different stages were coordinated to facilitate the swelling of the carbomer gel powder, forming a stable, high-performance gel system, maintaining wound moisture, and assisting tissue repair. The added stabilizer and ingredients constructed an interactive network, enhanced the stability of the dressing, continuously exerted antibacterial and repair properties, and stimulated cell growth and differentiation. Comparative Example 1 omitted pre-dispersion, and the carbomer gel powder and the compound containing rare earth elements and / or rare earth nanoparticles were unevenly mixed and agglomerated, interfering with cell metabolism and hindering wound healing. Comparative Example 2 added deionized water at one time during the reconciliation, resulting in uneven local concentration of the gel. High concentration areas may be toxic to cells, while low concentration areas cannot meet cell needs, slowing down the healing process. In Comparative Example 3, no stabilizer was added, and the hydrogel was easily delaminated and could not provide a stable healing environment, which affected the antibacterial and cell growth promoting effects and reduced the healing rate.

[0109] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention rather than to limit the same. Although the present invention has been described in detail with reference to the preferred embodiments, those skilled in the art should understand that they can still modify or replace the technical solutions of the present invention with equivalents, and these modifications or equivalent replacements cannot cause the modified technical solutions to deviate from the spirit and scope of the technical solutions of the present invention.

Claims

1. A method for preparing a rare earth-based nanocomposite hydrogel wound dressing, characterized in that: The following steps are included: S1. Adding gel powder to a dispersant for pre-dispersion to obtain a gel dispersion, and adding a rare earth element-containing compound and / or rare earth nanoparticles to a dispersant for pre-dispersion to obtain a rare earth dispersion; S2. Add the gel dispersion to the rare earth dispersion at a temperature of 30-40° C., add a portion of deionized water, stir for preliminary swelling, and then add the remaining deionized water while stirring until a gel-like dressing is formed; S3. Add a stabilizer to the gel dressing in S2, and stir to react to obtain a rare earth-based nanocomposite hydrogel wound dressing.

2. The method for preparing a rare earth-based nanocomposite hydrogel wound dressing according to claim 1, wherein: In S1, the gel powder is carbomer, and the rare earth element-containing compound and / or rare earth nanoparticles are one or more of organic or inorganic salts of lanthanum and cerium, and nanoparticles of lanthanum oxide and cerium oxide; The mass ratio of the gel powder to the compound containing rare earth elements and / or rare earth nanoparticles is 1-3:

1.

3. The method for preparing a rare earth-based nanocomposite hydrogel wound dressing according to claim 1, wherein: In S1, the dispersant is one of polyvinyl pyrrolidone, sodium lauryl sulfate, and polyethylene glycol; In S1, the mass of the dispersant in the gel dispersion is 10%-15% of the mass of the gel powder, and the mass of the dispersant in the rare earth dispersion is 8%-12% of the mass of the rare earth element-containing compound and / or rare earth nanoparticles.

4. The method for preparing a rare earth-based nanocomposite hydrogel wound dressing according to claim 1, wherein: In S1, the gel dispersion is pre-dispersed by ultrasonic dispersion at an ultrasonic frequency of 30-60 kHz for 10-30 minutes, and the rare earth dispersion is pre-dispersed by stirring at a stirring speed of 1200-1800 r / min for 10-30 minutes.

5. The method for preparing a rare earth-based nanocomposite hydrogel wound dressing according to claim 1, characterized in that: In S2, the volume ratio of the total amount of deionized water to the gel dispersion is 10:

1.

6. The method for preparing a rare earth-based nanocomposite hydrogel wound dressing according to claim 1, characterized in that: In S2, the stirring speed of the initial swelling is 60-80 r / min, and the stirring time is 10-20 min. After the remaining deionized water is added, the stirring speed is 80-100 r / min, and the stirring time is 20-30 min.

7. The method for preparing a rare earth-based nanocomposite hydrogel wound dressing according to claim 1, characterized in that: In S3, the stabilizer is one of sodium alginate and chitosan, and the amount of the stabilizer is 0.5%-2% of the total mass of the gel dressing.

8. The method for preparing a rare earth-based nanocomposite hydrogel wound dressing according to claim 1, characterized in that: In S3, the stirring reaction is carried out at a stirring speed of 120-180 r / min and the stirring is continued for 20-40 min.

9. A rare earth-based nanocomposite hydrogel wound dressing prepared by the method for preparing the rare earth-based nanocomposite hydrogel wound dressing according to any one of claims 1 to 8.

10. An application of a rare earth-based nanocomposite hydrogel wound dressing, characterized in that: The rare earth-based nanocomposite hydrogel wound dressing prepared by the preparation method of the rare earth-based nanocomposite hydrogel wound dressing according to any one of claims 1 to 8 is used in the preparation of drugs for promoting wound healing and tissue regeneration.

Citation Information

Patent Citations

  • Biofilms of rare-earth element contained chitosan and / or derivatives of chitosan

    CN102492182A

  • Hydrogel for promoting early wound healing and relieving scar formation

    CN108853573A

  • Preparation method of biodegradable wound dressing

    CN109260501A

  • Rare earth-based nano composite hydrogel wound dressing as well as preparation method and application thereof

    CN112604025A

  • Composite collagen-based wound dressing containing rare earth ions and preparation method thereof

    CN118079057A